COVID-19 AND ITS IMPACT ON TRADITIONAL TEXTILE INDUSTRIES AND ARTISAN WEAVING COMMUNITIES - Shweta; Yadav, Pragati Rani (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Varanasi is its textile industry which shows the true colors of unity among different communities. The Varanasi is known for its “BANARASI SILK” all across the globe, and remains intact in terms of fashion and culture. Evidently most of the weaving work is done by the Muslim communities in all over the place but it is majorly sold by the Hindus for the different purposes such as business and marriages and numerous rituals and daily life purposes. The study of Sarai Mohana village in order to study the impacts of the covid19 on the traditional weaving industry was the most appropriate way because it is the “village of weavers” and hence the best of cause-and-effect relationship can be derived from here and it can provide us with best possible results of the study. The paper tries to represent the different sections of the weaving community, both handloom and power looms and allied workers. The women of the weaving community are an important voice considering they are the backbone though invisible and often unrecognized as they face discrimination on wage grounds and social status as far as weaving work is concerned and during the lockdown they were the worst sufferers financially as well as socially.